Analisis Tanggung Jawab Hukum Dinas Pekerjaan Umum Bina Marga dalam Pemeliharaan Jalan di Jawa Timur - Vareli Denastyan Agpenta Putra; Sapto Hermawan; Asianto Nugroho (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
This study analyzes the legal responsibility of road organizers, legal protection for road users, and public participation in the maintenance of provincial roads in East Java. The background of this research is the significant road damage, covering 154 kilometers, which impacts the safety of road users and the smoothness of socio-economic activities. This research is based on Law Number 22 of 2009 on Traffic and Road Transportation (UU LLAJ) and Law Number 38 of 2004 on Roads, which regulate the obligation of road organizers to ensure safe and adequate infrastructure. The research method used is a juridical normative approach with an analysis of legislation, using primary and secondary legal materials, with data collected through library studies and deductive analysis. The results show that the government is legally obligated to repair damaged roads, place warning signs on roads that have not been repaired, and allocate funds to prevent traffic accidents. However, various challenges such as limited budgets and geographic conditions affect the implementation of these obligations. Additionally, the Citizen Lawsuit mechanism grants the public the right to sue negligent organizers. This study recommends strengthening road maintenance management based on risk, improving transparency and accountability, and empowering the public to ensure safe roads that support regional economic growth.